Synthesis of Chitosan Nanocomposite Materials Grafted with MWCNTs for the Removal of Tetracycline Pharmaceutical from Water Samples - Milton Shabeng Kgoete; Conny Putsane Mokgohloa; Lutendo Evelyn Macevele (Colloids and Interfaces, 2025)
Pharmaceutical contaminants such as tetracycline pose an increasing threat to aquatic ecosystems and human health as a result of their persistence in water sources and their contribution to antibiotic resistance. This study developed chitosan nanocomposites by incorporating functionalised and nitrogen-doped multi-walled carbon nanotubes (FMWCNTs and NMWCNTs) for the removal of tetracycline pharmaceutical contaminants from water. The composites were characterised with FTIR, SEM, XRD, BET, UV–Vis, and TGA under various conditions (pH, adsorbent dosage, concentration, contact time, and temperature). Optimal tetracycline removal (85%) was achieved with pH 6, 2 g/L adsorbent dose, 10 ppm concentration, and 30 min contact time. The FMWCNT–chitosan composite could be recycled five times with an adsorption loss of only 2%. The FMWCNT–chitosan composite showed the good adsorption efficiency of 82% in the presence of counter ions and 70% in a binary system. The adsorption process followed the Langmuir isotherm (263 mg/g), indicative of monolayer adsorption and pseudo-second-order kinetics. Among the nanocomposites prepared, the FMWCNT–chitosan composite showed the highest performance, removing more than 85% of tetracycline from water samples.